5-epi-Sinuleptolide from Soft Corals of the Genus Sinularia Exerts Cytotoxic Effects on Pancreatic Cancer Cell Lines via the Inhibition of JAK2/STAT3, AKT, and ERK Activity - Wan-Chi Tsai (MDPI AG, 2021)
Pancreatic ductal adenocarcinoma is one of the most lethal malignancies: more than half of patients are diagnosed with a metastatic disease, which is associated with a five-year survival rate of only 3%. 5-epi-Sinuleptolide, a norditerpene isolated from Sinularia sp., has been demonstrated to possess cytotoxic activity against cancer cells. However, the cytotoxicity against pancreatic cancer cells and the related mechanisms are unknown. The aim of this study was to evaluate the anti-pancreatic cancer potential of 5-epi-sinuleptolide and to elucidate the underlying mechanisms. The inhibitory effects of 5-epi-sinuleptolide treatment on the proliferation of pancreatic cancer cells were determined and the results showed that 5-epi-sinuleptolide treatment inhibited cell proliferation, induced apoptosis and G2/M cell cycle arrest, and suppressed the invasion of pancreatic cancer cells. The results of western blotting further revealed that 5-epi-sinuleptolide could inhibit JAK2/STAT3, AKT, and ERK phosphorylation, which may account for the diverse cytotoxic effects of 5-epi-sinuleptolide. Taken together, our present investigation unveils a new therapeutic and anti-metastatic potential of 5-epi-sinuleptolide for pancreatic cancer treatment.